2011
DOI: 10.1016/j.neuroimage.2010.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive profile and brain morphological changes in obstructive sleep apnea

Abstract: Obstructive sleep apnea (OSA) is accompanied by neurocognitive impairment, likely mediated by injury to various brain regions. We evaluated brain morphological changes in patients with OSA and their relationship to neuropsychological and oximetric data. Sixteen patients affected by moderate-severe OSA (age: 55.8±6.7 years, 13 males) and fourteen control subjects (age: 57.6±5.1 years, 9 males) underwent 3.0 Tesla brain magnetic resonance imaging (MRI) and neuropsychological testing evaluating short and long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
188
4
18

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(229 citation statements)
references
References 56 publications
19
188
4
18
Order By: Relevance
“…Our present study revealed that patients with COPD had reduced GM volume in a number of brain regions, which were mainly confined to the limbic/paralimbic structures and frontal cortices, compared with healthy controls. These findings are consistent with those in patients with obstructive sleep apnea, 18,19,24 congenital central hypoventilation syndrome, and pediatric heart failure, 25 and in high-altitude residents. 20 Moreover, patients with COPD exhibited poorer performance on visuospatial and visual reproduction tasks.…”
Section: Discussionsupporting
confidence: 88%
“…Our present study revealed that patients with COPD had reduced GM volume in a number of brain regions, which were mainly confined to the limbic/paralimbic structures and frontal cortices, compared with healthy controls. These findings are consistent with those in patients with obstructive sleep apnea, 18,19,24 congenital central hypoventilation syndrome, and pediatric heart failure, 25 and in high-altitude residents. 20 Moreover, patients with COPD exhibited poorer performance on visuospatial and visual reproduction tasks.…”
Section: Discussionsupporting
confidence: 88%
“…In a study of elderly women, higher AHI and duration of sleep in apnea or hypopnea were associated with cognitive impairment. 1 Prior imaging studies further support a role for OSA in the development of brain atrophy 21,22 and cerebral white matter disease. [23][24][25] SWS has not been previously examined as a risk factor for the pathologic correlates of dementia.…”
Section: Methods Study Population the Honolulu-asia Agingmentioning
confidence: 89%
“…44 Younger age is protective of cognitive impairment in the presence of SDB. 45,46 Age and premorbid intelligence are important considerations in investigating the effect of SDB on neuropsychological function and likely contribute to the previously observed heterogeneity of results across the studies. In the current research, these factors were accounted for and their importance confirmed by the study data.…”
Section: Discussionmentioning
confidence: 99%